Correlation between duration of diabetes mellitus type 2 with erectile dysfunction - Firmansyah, Rio; Nugraha, Dimas Pramita (International Journal Labs, 2024)
Diabetes mellitus (DM) type 2 was one of systemic disease that cause high morbidity and mortality rate in Indonesia. This time Erectile Dysfunction (ED), one of DM type 2 complication become a serious issue because firstly the incidence of erectile dysfungtion is high. 50%-80% of people with DM type 2 have ED, Secondly this problem impact to patient life medicaly (psychology and infertility) as well as nonmedicaly (materials long divorve and family). Etiology of ED ed DM type 2 are diabetic neuropathy, diabetic angiopathy, psychis and hormonad factor. All of them earelated to duration of DM type 2. The research aims to learn about correlation between duration of DM type 2 with ED on Arifin Achmad Hospital pekanbaru. This study use cross sectional method the population were all of out patient care in Arifin Achmad Hospital. The study held on July – Agust 2013 with nonprobability sampling technique, consecutive sampling, and there are 42 responden. Based on the contingency coefficient test results, there were correlation between of duration of DM type 2 with ED (p= 0,012, r= 0,453). There is correlation between duration of DM type 2 with ED, with the strength of correlation and the direction of the positive correlation between duration of DM type 2 with ED.